PENERAPAN METODE USABILITY UNTUK MENENTUKAN TINGKAT KEPUASAN PADA SISTEM MOBILE M-BANKING BRIMO - Haristina Putri, Maulida; Sanjaya, M. Rudi; Kurniawan, Dedy; Indah, Dwi Rosa (AI Society & STMIK Indonesia, 2025)
This study aims to analyze the level of user satisfaction with the BRImo Mobile Banking application using the usability method.Research fokus includes usability aspects:learnability, efficiency, memorability, errors, and satisfaction. Data obtained through questionnaires distributed to 252 respondents in Palembang City.The results showed learnability had communalities of 0.599-0.703 and correlations of 0.432-0.514, while efficiency achieved communalities of 0.585-0.649 with correlations of 0.415-0.550.In contrast,errors had a significant negative impact,with a correlation of -0.352 to -0.488, indicating the more errors,the lower user satisfaction.Memorability shows communalities values between 0.511 to 0.663. BRImo application features, such as efficiency in transaction access speed (efficiency_2 and efficiency_3) which have a correlation of 0.498-0.550,as well as overall ease of access (learnability_5) with a correlation of 0.467,have a positive influence on user satisfaction. Technical issues such as bugs,crashes, and slow applications negatively impact user satisfaction,with errors_5 having low communalities of 0.445 and a significant negative correlation of -0.382,indicating technical errors strongly influence user